Oxford international lower secondary english student book 2 for grade 7 - Danihel, Emma (Karachi: Oxford University Press., 2022)
The Oxford International Lower Secondary English: Student Book 2 for Grade 7 builds on previous learning, helping students develop more advanced reading, writing, and analytical skills. It introduces a wider range of text types, including fiction, non-fiction, drama, and poetry, encouraging students to engage critically with diverse genres. The book places a strong emphasis on refining grammar, punctuation, and vocabulary, while also focusing on effective communication, both written and verbal. Through structured lessons and activities, students enhance their ability to write essays, analyze literature, and respond thoughtfully to texts, preparing them for the challenges of secondary-level English.